Influence of Curvature Radius on Mechanical Behavior of Extruded 6061-T6 Aluminum in Roll Bending - Mauricio da Silva Moreira; Carlos Eduardo Marcos Guilherme; João Henrique Corrêa de Souza; Elizaldo Domingues dos Santos; Ana Pavlovic; Liércio André Isoldi (Journal of Applied and Computational Mechanics)
This article presents a numerical study encompassing the mechanical behavior prediction during the roll bending process applied to four distinct profiles of extruded 6061-T6 aluminum, considering different radii of curvature. The numerical simulations were conducted using the ANSYS® software, based on the finite element method, adopting the three-dimensional SOLID187 finite element. The employed computational model was developed and validated by Moreira et al. [1]. The obtained results demonstrate consistent patterns regarding stresses and displacements for the different radii of curvature. As the radius of curvature decreases, the von Mises stress tends to increase, approaching the material's strength limit. This phenomenon is critical for identifying points of maximum stress and ensuring adequate safety margins to prevent structural failures. Displacements along the profiles were also monitored, providing relevant information about its evolution at different radii of curvature and allowing curve fitting for these displacements in each profile investigated. Therefore, these consistent patterns observed can help to determine the direct influence of curvature on resulting defects, contributing to an in-depth understanding of the mechanical behavior of these profiles.